We will learn how to prove the property of the inverse trigonometric function 2 arcsin(x) = arcsin(2x\(\sqrt{1 - x^{2}}\)) or, 2 sin\(^{-1}\) x = sin\(^{-1}\) (2x\(\sqrt{1 - x^{2}}\)).
Proof:
Let, sin\(^{-1}\) x = α
Therefore, sin α = x
Now, sin 2α = 2 sin α cos α
sin 2α = 2 sin α \(\sqrt{1 - sin^{2}α}\)
sin 2α = 2x . \(\sqrt{1 - x^{2}}\)
sin 2α = 2x\(\sqrt{1 - x^{2}}\)
Therefore, 2α = sin\(^{-1}\) (2x\(\sqrt{1 - x^{2}}\))
2 sin\(^{-1}\) x = sin\(^{-1}\) (2x\(\sqrt{1 - x^{2}}\)).
or, 2 arcsin(x) = arcsin(2x\(\sqrt{1 - x^{2}}\)) Proved
● Inverse Trigonometric Functions
11 and 12 Grade Math
From 2 arcsin(x) to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Oct 04, 24 09:47 AM
Oct 04, 24 01:28 AM
Oct 03, 24 03:22 PM
Oct 03, 24 02:22 PM
Oct 03, 24 01:13 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.